Surface magnetic properties and giant magnetoimpedance effect in Co-based amorphous ribbons. (July 2017) - Chizhik, A.; Vega, V.; Mohamed, Abd El-Moez A.; Prida, V.M.; Sánchez, T.; Hernando, B.; Ipatov, M.; Zhukova, V.; Zhukov, A.P.; Stupakiewicz, A.; Domínguez, L.; González, J.
Abstract: Correlationship between surface magnetic properties studied using the MOKE technique and giant magnetoimpedance effect (GMI) of nearly-zero magnetostrictive Co66.5 Fe3.5 Si12.0 B18.0 amorphous ribbons in as-cast state has been investigated in the frequency range of 10 MHz–1.5 GHz. It was found that the surface anisotropy is different in the sides of the ribbon: it is transversal to the ribbon axis with multiple domain walls in one side and axial with a single domain wall in the other. The effect of permanent bias current on surface domain structure was investigated and it was found that the multidomain transversal is very sensitive to the bias current while the axial anisotropy is practically not affected by the applied bias current. This finding can be applied in design of highly sensitive material for magnetic sensors. Highlights: The domain structure is different in two sides of the ribbon. As increasing frequency of electric current along ribbon, surface layer thickness and permeability change. The values of anisotropy field are around of 400 A/m for "in" side and 900 A/m for "out" side.